Perbandingan Mutu Air di Bendungan yang Berada di Provinsi Jawa Timur - Eka Wardhani; Athaya Zahrani Irmansyah; Syania Budi Oktaviani; Aulia Ulfie Rindiantika (Jurnal Serambi Engineering, 2023)
A dam is a body of water that is relied upon in raw water supply. Many dams have deteriorated due to human activities in their catchment areas. East Java Province Government is currently trying to improve the function of the dam as a water reserve in the dry season. This study aims to compare water quality in nine dams located in East Java Province. The Telaga Pasir and Gonggang Dams are in Magetan Regency. The Notopuro, Saradan, Kedung Brubus, and Dawuhan dams are in Madiun Regency. Kedung Bendo, Pondok, and Sangiran dams are in Ngawi Regency. The method for determining water quality is based on KepMenLH No 115/2003 concerning guidelines for determining water quality status. Water sampling was carried out on January 24 to February 7, 2022, representing the dry season by grab sampling. Water samples were taken from the part of the dam with a pool of water. The results showed that the water quality of all dams was categorized as good to slightly polluted, with index values ranging from 0.80 to 3.10. The cause of water quality being lightly polluted is the BOD, COD, Free Chlorine, Arsenic, Cadmium, Copper, Ammonia, and Nitrite, which do not meet quality standards. The presence of these parameters is predicted to originate from the activities of residents around the catchment area, such as settlements and agriculture.